PEMETAAN CAPAIAN PEMBELAJARAN DAN MATERI AJAR PAI DAN BUDI PEKERTI ELEMEN Al-QURAN DALAM KURIKULUM MERDEKA - Aulia, Muhammad Hizba; Fakhruddin, Agus; Surahman, Cucu (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2024)
Al-Quran as an element of PAI and Budi Pekerti in the Merdeka Curriculum has continuous learning outcomes and teaching materials from primary to secondary education levels. However, the reality on the ground shows that the level of Quran literacy among students in Indonesia is still low. To overcome this, it is necessary to map based on Quran literacy components such as reading according to tajweed, writing, memorizing and interpreting. This is the purpose of this study to ensure that the Learning Outcomes and Teaching Materials for PAI and Budi Pekerti in the Merdeka Curriculum are in accordance with the development of students and the concept of Islamic teachings about the Quran. This research is a qualitative research with content analysis method. The data sources are curriculum documents and PAI and Budi Pekerti textbooks for the Merdeka Curriculum version, which are analyzed through a document study approach. The results of the study provide findings in the form of mapping learning outcomes and teaching materials for PAI and Budi Pekerti elements of the Al-Quran in the Merdeka Curriculum on the Al-Quran literacy component from primary to secondary education levels.